Implementasi Web Scrapping pada Website Eduesia.Com untuk Pengukur Kesenjangan Jumlah Mahasiswa Perguruan Tinggi di Indonesia - Yuri Pramana; Wira Munggana (ULTIMA InfoSys, 2015)
Education is an important asset for the future of each individual, community, nation, and world. However, not everyone can have the same opportunity as the field of economic and geographic constraints that trigger gaps in the public assessment of the quality of one’s intellectual. Based on data provided by UNESCO, Indonesia recorded no. 4 from other ASEAN countries, in the level of Gross Enrolment Ratio. The research process is intended to form a picture of educational inequality at the college level in every region in Indonesia. This study was made with Web scrapping’s techniques and produce a website that presents a valid and accurate information and analysis of the ratio of Gross Enrolment Ratio to show the level of participation at the college level. Index Terms - Data Collection, UMN, Web Crawling, Data Cleansing, Web Scrapping.